Pengaruh Keterlibatan Konsumen Dan Atribut Produk Terhadap Kepuasan Konsumen Dan Kepercayaan Merek Serta Dampaknya Pada Loyalitas Merek Kosmetik - Fatonah, Siti (-)
The objective of this study are: (1) analyzing the influence of type of involvement to brand trust in every cosmetic product categoiy in East Java; (2) analyzing the influence of level of involvement to brand trust in eveiy cosmetic product category in Bast Java; (3) analyzing the influenre of attribute product to brand trust in eveiy cosmetic product category in F.ast Java:, (4) analyzing the  influence of type  of involvement to customer satisfaction in every cosmetic product category in East Java; (5) analyzing the influence of level of involvement to customer samfaction in  every  cosmetic product category in East Java; (6) analyzing the influence of attribute product to customer satisfaction in every cosmetic product category in East Java; (7) analyzing the influence of customer satisfaction to brand loyalty in every cosmetic product category in East Java; (8) analyzing the influence of brand trust to brand loyalty in every cosmetic product category  in F.ast Java and; (9) analyzing the influence of customer satsfaction to brand trust in every cosmetic product category in East Java.Populations Qf this study are women age between 20 - 50 years old that lives in East Java during the research period, using cosmetic everyday including moistumer, foundation, powder, blush on, eyes shadow, eye  brows  pencil and lipstick. The respondent is taken by snowball sampling technique to assure that each of the respondents is the member of the population. All data is analyzed with AMCS version4.01 using Structural Equation Model.The results of this study are: (1) ffpe of involvement is positively influencing customer satisfaction; (2) level of involvement is positively  influencing customer satisfaction; (3) Attribute product is positively irrfluencing customer safisfaGbon; (4) type of involvement is positively influencing brand trust (5) level of involvement is positively influencing brand trust (6) attribute product is pooitively infiuencing brand trust;(7) customer satisfaction is positively influencing brand loyalty; (8) brand trust is positively influencing brand loyalty and; (9). customer  satisfaction is positively influencing brand trust.Keywords: customer satisfaction, brand trust, brand loyalty, involvement attribute product